Hepatitis B virus DNA in Blood Donors Positive of Anti-Hepatitis B Core Antibodies and Negative for Surface Antigen in Hawler Major Blood Bank, Kurdistan Region, Iraq - Hassan, Rasha N.; Hussain, Ali H. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Occult Hepatitis B virus infection (OBI) among blood donors is an important medical concern.Objectives: This study was done to detect the presence of occult hepatitis B virus infections among blood donors with negative hepatitis B surface antigen and positive total anti-hepatitis B core antibodies in Hawler Major Blood Bank in Hawler city/Kurdistan Region of Iraq.Methods: A total number of 12,185 blood donors in Hawler Major Blood Bank were screened for HBsAg and total anti-HBcAb using ELISA technique, and then positive results were retested by confirmatory technique by Chemiluminescence assay. All HBsAg-/HBcAb+ were selected as the study group; HBV DNA was tested among HBsAg-/HBcAb+ by conventional PCR and Real time-PCR. Clinical and demographic data of study group were recorded.Results: Among the 12,185 blood donors, HBsAg was positive in 27 (0.22%) donors using Chemiluminescence assay, the frequency of HBs Ag -/ HBc Ab+ was 276 (2.27%), and then the total prevalence of HBV infection in all blood donors was 2.49%. Among the 276 HBs Ag-/HBcAb+, occult hepatitis B virus infection (OBI) was positive in 39.1% (108/276) using conventional PCR and Real time-PCR techniques, while the prevalence among all blood donors (n=12,185) was 0.09%. Testing of HBV-DNA in HBs Ag -/ HBc Ab+ group for OBI was done by qualitative PCR (positive HBV-DNA=102/276) or by quantitative Real time-PCR (positive HBV-DNA=108/276).Conclusions: The OBI is frequently detected among blood donors in Hawler city especially those have HBsAg-/HBcAb+, and the total anti-HBcAb is an essential serological marker for screening HBV among blood donors. The risk factors for developing OBI among blood donors should be elucidated.